Using Brief Experimental Analysis (BEA) to Identify Effective Math Interventions - Campbell, Vincent; DeLapp, Christina (My University, 2011)
The purpose of this study was to identify math computation fluency interventions for three low achieving elementary school students using Brief Experimental Analysis (BEA) methodology.
Color poster with text and graphs.
Keywords: Mathematical ability in children; Brief experimental analysis; National Assessment of Educational Progress (Project)--Statistics; Posters